EFFICACY OF ANANDA YOGA CHURNA IN THE MANAGEMENT OF MOOTRASHMARI (UROLITHIASIS) - A CLINICAL STUDY - Yati, *Tiwari; Kamleshwar, Prasad; Madhu, Singh (International Journal of Ayurveda and Pharma Research, 2016)
According to modern science, the formation of stone in urinary system is one of the main problems of urology. The cause and mechanism of their formation is still uncertain. On one hand surprisingly stone does not always form when such factors are present and on the other hand stones may develop when factors are apparently absent too. Treatment of calculi in modern science is only surgery and very less medicines are available for this purpose. After surgery, the probability of reoccurrence of calculi is same as previously, so it is negative aspect of this science. But in ancient medical, after treatment and removal of stone, the chances of recurrence are rarely occurs. In this research work, subjective symptoms like pain, burning micturiton, haematuria, dysurea, tenderness and fever are reduced very significantly and their recurrence does not occurs during trial of drug. Maximum patients belong to the category of renal and ureter culculi and efficacy of drug are also maximum observe on renal and as well as ureter. On the basis of size of calculi i.e. 6 mm to >10 mm, the efficacy of drug are also observed and result exhibited as 66 percent to 100 percent. So, the overall result in this research work is that, 72 % patients are cured, 20% patients are improved and only 8% patients are unchanged. Hence, the classical medicine Anand yoga churna for Mutrashmari is best the medicine because its efficacy is very significant on both subjective and objective parameters, cast effective, easy availability and also removed the negative aspect of modern medical science i.e. recurrence of calculi.